Aktivitas Antifungi Nanopartikel Ekstrak Kulit Buah Kakao terhadap Candida auris Multiresisten - Hidayat, Fahmi Nur; Putra, Rizky Ananta (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aimed to evaluate the antifungal activity of nanoparticles derived from cocoa pod husk (Theobroma cacao L.) extract against multidrug-resistant Candida auris, an emerging pathogen with high resistance to various antifungal agents. Cocoa pod husk, commonly considered an agricultural waste, contains bioactive compounds such as flavonoids, alkaloids, and polyphenols with potential antifungal properties. To enhance bioavailability and effectiveness, the extract was formulated into nanoparticles using a green synthesis approach with natural polymers. Antifungal activity was assessed using the disc diffusion method and determination of Minimum Inhibitory Concentration (MIC). Results demonstrated that cocoa husk extract nanoparticles produced significant inhibition zones against multidrug-resistant C. auris, with lower MIC values compared to conventional extracts. These findings highlight the potential of cocoa pod husk waste as a sustainable source of bioactive compounds for antifungal nanoparticle formulations, providing an eco-friendly strategy for both agricultural waste utilization and medical application.